Modeling and analysis of batteryless off-grid photovoltaic with adaptive multi-motor - I Wayan Sutaya; Ida Ayu Dwi Giriantari; Wayan Gede Ariastina; I Nyoman Satya Kumara (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper presents a model of a batteryless off-grid photovoltaic (PV) system with an adaptive multi-motor load. This model is developed as an effort to enhance the power output of batteryless off-grid PV systems for motor loads. Instead of using a single large-capacity motor, as commonly done in previous studies, the model distributes the load into several smaller motors and controls them adaptively. This approach allows for better control of the total load impedance to support maximum power point (MPP) tracking. A case study involving three three-phase induction motors, each with an operating power of 200 W, is conducted, where the power production of the proposed model is analysed by comparing it with the theoretical MPP and a fixed-load motor system that represents a single large motor. Under 1000 W/m² irradiance and using an 852 Wp PV array, the proposed model achieves a power output of 842 W, which corresponds to 98.83% of the MPP. In contrast, the system without this model only generates 298 W, or just 35.02% of the MPP. The testing process spans a 5-second period during the motor starting state. The power production analysis of the proposed model is presented in graphical form using MATLAB/Simulink.